IMPLEMENTASI KARAKTER PEDULI LINGKUNGAN DI SDN 13 LOLONG BELANTI PADANG - Efendi, Nofriza; Baskara, Refli Surya; Fitria, Yanti (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
The phenomenon of students who clean the school grounds before the bells enter the lesson, pay attention to the cleanliness conditions around the seat and before coming home from school the students always water the flower plants. All these activities are carried out consciously without a teacher's order. This study aims to analyze the implementation of the value of caring for the environment through learning in the classroom, the implementation of the value of caring for the environment through extracurricular activities and the obstacles found in the implementation of the value of caring for the environment in elementary schools. This type of research is a qualitative research with a case study approach. Informants are determined using Purposive Sampling. the research results obtained findings that (1) Internalization of the value of environmental care in learning planning in the form of compiling teaching devices such as syllabus, Learning Implementation Plan (RPP) and learning media, the device has been analyzed in advance about the value content contained in the material to be taught (2 ) Implementation of the value of environmental care is integrated through learning in the classroom and through routine school activities, spontaneous activities and through exemplary behavior (3) Obstacles found in the implementation of the value of environmental care consist of internal factors such as, bad habits of students do not care about personal hygiene, lack of knowledge students to choose the scattered garbage. External factors such as lack of adequate facilities and lack of collaboration between parents and teachers in schools.